Improvement of Strength and Strain Characteristics of Lightweight Fiber Concrete by Electromagnetic Activation in a Vortex Layer Apparatus - Evgenii M. Shcherban’; Sergey A. Stel’makh; Alexey Beskopylny; Levon R. Mailyan; Besarion Meskhi; Anatoly Shuyskiy (Applied Sciences, 2021)
The relevant problem of choosing effective materials for enclosing structures is compliance with the requirements of increased thermal resistance, reduced mass of buildings and structures, and reduced material consumption, labor intensity, and construction costs. These requirements are satisfied by structures made of lightweight fiber-reinforced concrete, which are the subject of attention of many scientists and engineers. One of the most rational requirements for industrial use is the activation of untreated components of the concrete mixture. This article is devoted to studying the influence of the activation of fiber-reinforced concrete elements in the vortex layer apparatus on concrete strength and structural characteristics. The effect of the raw component processing time of the concrete mixture on the strength and deformation characteristics of the lightweight fiber-reinforced concrete was studied. The optimal processing time for the cement–sand mortar in the VLA-75-85s was determined. It was shown that the activation of the vortex layer in the apparatus leads to an increase in strength from 27% to 61% and an improvement in the deformation characteristics of lightweight fiber-reinforced concrete by up to 12%. Furthermore, it was found that the use of activation in VLA leads to an increase in the coefficient of constructive quality for all experimentally determined strength characteristics of lightweight fiber-reinforced concrete by up to 27%.